Three Delays Model and its Determinants for Maternal Death: A Descriptive Cross-Sectional Study - Joshi, Rijuta; Jaiswal, Ekta; Timalsina, Gyanu; Byanjankar, Sunita (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Despite significant improvements in reducing maternal mortality in Nepal, preventable deaths persist due to gaps in timely care-seeking, access, and service delivery. The ‘Three Delays Model’ offers a framework to examine delays contributing to maternal mortality and guide targeted interventions. This study was done to identify the types of delays, patterns, and characteristics contributing to these maternal deaths. Methods: A descriptive cross-sectional study of maternal deaths was conducted at Patan Academy of Health Sciences, Patan Hospital, Nepal, from July 2021 to July 2024 after ethical clearance (Reference number: drs 2506202030). Data were extracted from hospital records and maternal mortality audit reports. The ‘Three Delays Model’ was applied to categorize barriers: delay 1-decision to seek care, delay 2-reaching care, and delay 3-receiving adequate care. Descriptive analysis was performed using Microsoft Excel. Results: This study identified 16 maternal deaths over three years, with the highest mortality among primigravida women in late pregnancy and postpartum periods. Indirect causes were predominant than direct obstetric causes. The indirect causes of maternal death were severe COVID-19 pneumonia, acute respiratory distress syndrome, pneumothorax, pulmonary embolism, and septicemia secondary to lupus nephritis. Delay in seeking health care was the most prevalent, followed by the delay in receiving care. Conclusions: Maternal deaths remain influenced by behavioral and systemic factors, with Delay 1 as the most prevalent underlying cause, followed by Delay 3.